Simulation of the power supply system with an active filter, controlled by the optimization algorithm - Ягуп, Екатерина Валериевна (Eastern-European Journal of Enterprise Technologies, 2016)
The presence of an inductive load in the grid gives rise to a reactive power, which adversely affects the quality of electric energy and operation of its consumers. The use of active filters with controlled switches allows one to reduce the phase shift of the grid current to almost zero. The power supply system under study consists of three main units: a single-phase system with active-inductive load and active-inductive internal resistance of power sources, the active power filter and the filter control system using pulse width modulation. The filter under consideration is a half-bridge inverter. It consists of two capacitors, two controlled switches - IGBT-transistors and the inductor, which smoothes the current supplied. As a result of search engine optimization, it is necessary to find such values of parameters that compensate the reactive power and minimize the grid current strength. Optimization parameters are the difference of voltage across the capacitors of the half-bridge inverter in the initial and final points of simulation and the peak value of the sine-wave generator. For this, a special visual model was developed by means of the MATLAB application package and the Simulink graphical simulation environment using search engine optimization. As a result of the computer simulation, the reactive power value was reduced to almost zero, the voltage across the capacitors stabilized, and the grid current strength was reduced to a possible value.